PENERAPAN KRIPTOGRAFI RSA UNTUK MENGATASI PEMALSUAN DALAM INDUSTRI PENERBITAN BUKU - Ngiliyun, Ahmad; Rosidin, Rosidin; Nugraha, Deni (TECHNOVATAR Jurnal Teknologi, Industri, dan Informasi, 2024)
This study aims to develop a book publishing information system that can assist lecturers in publishing their academic works more efficiently and securely. The system implements the Rivest-Shamir-Adleman (RSA) cryptographic algorithm to protect book data from unauthorized access, as well as to prevent counterfeiting and copyright infringement. With the encryption applied, only authorized parties can access sensitive information. The implementation of this system has proven to increase efficiency in the book publishing process, reduce administrative obstacles, and enhance authors' confidence in the security of the system. It is expected that this system will boost academic productivity and maintain the integrity of lecturers' intellectual works.